Relational pedagogy and the policy failure of contemporary Australian schooling: activist teaching and pedagogically driven reform. (3rd July 2022) - Hickey, Andrew; Riddle, Stewart; Robinson, Janean; Down, Barry; Hattam, Robert; Wrench, Alison
ABSTRACT: This paper considers the implications of the current landscape of education policy reform in Australian schooling. We argue that the decontextualisation of education policy enactments and the eschewing of concerns relevant at the local level of the school over the past two decades have prompted various reform agendas to fail. We contend that recognition of the deep contextualisation of schools is paramount in any attempt at renewal. Therefore, it is at the local school-level that reform agendas can and should be directed by the pedagogical and innovative work of educators. We focus on 'relational pedagogy' because it offers opportunities to enact school-wide reform and enhance the professional capacities of educators as pedagogical innovators. Contemporary education reform agendas are best situated and registered within school sites and relational pedagogy stands as a deeply contextualised provocation for enacting school renewal.